Applying a method for measuring the performance of university-industry R&D collaborations: case study analysis - Fernandes, Aldora Gabriela Gomes (2019)
Collaborations between university and industry are possibly the most important strategic instrument used to increase the efficiency and effectiveness of industrial investments in Research and Development (R&D), and have been increasing, which assigns even more importance to the need for measuring their performance. Therefore, a method to measure university-industry R&D collaborations, named MPUIC, developed based on Design Science Research methodology (DSRM), was applied and validated through a case study. This paper firstly describes some improvements made to the previously developed MPUIC method before its application to a large program between the University of Minho and Bosch Car Multimedia (Portugal). The MPUIC method adopted a weighted scoring approach, and is composed by 31 performance indicators, distributed through the program management life cycle. Secondly, the performance measurement of the case study program is conducted, resulting in a score of 4.4 in a scale of 1 to 5, where 5 indicates "very high" performance. Finally, a questionnaire was administered to evaluate the developed method and, from the 31 performance indicators that compose the method, 29 were evaluated as having a level of relevance above 3 in a scale of 1 to 5 and, from these, 19 were evaluated as having a level of relevance equal to or above 4.